Description of students' Integrated Science Process Skills on Friction Material on a Flat Field - Mashelin Wulandari; Ricky Purnama Wirayuda; Febritia Aldila; Retno Wulandari (Lensa: Jurnal Kependidikan Fisika, 2020)
Science Process Skills have an important function in the process of student curiosity and scholarship, so it is necessary to do a description of students' science process skills. This study aims to describe students' integrated science process skills on friction material on a flat plane at SMPN 9 Muaro Jambi. The observed science process skills consist of ten observation indicators, namely experimental analysis, planning experiments, conducting experiments, describing the relationship between variables, defining variables operationally, making data tables, obtaining and processing data, making hypotheses, identifying variables and making graphs. This type of research is qualitative research with descriptive type. The research subjects were students of class VIII at SMP Negeri 9 Muaro Jambi which consisted of class VIII D and VIII E. The sampling technique was total sampling where the total sample was 40 students. While the data collection technique uses observation sheets that have been validated by a team of experts. The data that has been obtained were analyzed using descriptive statistical techniques with the help of IBM SPSS statistics software. The results of the research on students' mastery of integrated science process skills in the friction practicum on the flat plane were classified into the good category with a percentage of 57.5%. This means that students have good science process skills, because most students are skilled at doing practicum based on experimental indicators. The conclusion of this study shows that the integrated science process skills possessed by students are categorized as good.